2020
DOI: 10.31410/balkans.jetss.2020.3.2.163-170
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Robots and Artificial Intelligence on Service Quality in the Hotel Industry

Abstract: Service robots and artificial intelligence promise to improve the service quality. Robotics in combination with rapidly improving technologies like artificial intelligence, bring opportunities for a wide range of innovations that have the potential to change service quality in hotel industry. Based on an extensive literature review, this article presents the acceptance of service robots in hotel industry. The paper acknowledges that the adoption of the robots and artificial intelligence on service quality is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Tangibility refers to physical facilities, equipment, and appearance of robots in r-services cf. [55], as one of the most common factors of r-service quality [66]. In the reviewed studies, tangibility is a significant dimension that determines overall service quality [13], [36], service expectations [59], and willingness [27] and intention to use robots [5], [11], [37].…”
Section: R-service Quality Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tangibility refers to physical facilities, equipment, and appearance of robots in r-services cf. [55], as one of the most common factors of r-service quality [66]. In the reviewed studies, tangibility is a significant dimension that determines overall service quality [13], [36], service expectations [59], and willingness [27] and intention to use robots [5], [11], [37].…”
Section: R-service Quality Constructsmentioning
confidence: 99%
“…Concerning qualitative research, online [23] and offline interviews have mainly been the latter of which includes open-ended interviews [27], semi-structured interviews [5], [24], and focus-group interviews [31]. A few studies also use literature analysis [51], [66] to identify factors impacting r-service quality. Regarding quantitative studies, online surveys are the most widely used by researchers.…”
Section: Survey Administrationmentioning
confidence: 99%
“…It has also become a tool for generating revenue, with the robot charging a fee for delivering items, such as coffee from the lobby cafe that would not have been able for delivered before. Yang et al ( 2020), Jiang and Wen (2020), Marković et al (2020) found that during the pandemic, some hotels use Artificial Intelligence (AI) technology to improve their service quality.…”
Section: Technological Innovation In the Accommodation Sectormentioning
confidence: 99%
“…Hotels in tourist areas need to adapt to changing market conditions, upgrade their facilities, and diversify their offerings to remain competitive and attract visitors. The Experience Economy Theory posits that in an increasingly commoditized world, businesses can differentiate themselves by creating memorable experiences for customers (Alananzeh, 2022;Marković et al, 2020). This theory is highly relevant to hotels and tourism, as travelers seek unique and immersive experiences.…”
mentioning
confidence: 99%